ASTM Designation: D 5032-97 (reapproved 2003) : Standard practice for maintaining constant relative humidity by means of aqueous glycerin solutions. (S.l. : ASTM.)
Controlled relative humidity environments are important for conditioning materials for shelf-life studies or for investigating the change in physical or dielectric properties after exposure. The use of aqueous-glycerin solutions reduces the possibility of contamination of the materials or corrosion of electrode systems which would be more likely to result from saturated salt or acid water solutions. Applicable material specifications should state the exposure conditions, including time, temperature and relative humidity, that a material should be subjected to before subsequent testing. Typical conditions are given in Practice D 618.